EFFECTIVENESS OF PHYSICAL THERAPY SERVICES THROUGH TELEMEDICINE DURING THE COVID-19 PANDEMIC: SYSTEMATIC REVIEW - Viorentina Yofiani; Amal Chalik Sjaaf (Universitas Pahlawan, 2021)
The Covid-19 pandemic has greatly impacted physical therapy services. In the context of the physical distancing strategy, physical therapy services at health care centers are very limited. Telemedicine or telerehabilitation offers a solution that is expected to be realized by physical therapy services so that it can be accessed by patients with impaired function and movement from home and can reduce the risk of the getting Covid-19 virus infection during this pandemic. This study aims to systematically review the effectiveness of physical therapy services through telemedicine or telerehabilitation during Covid-19 pandemic. The method used is a systematic review done by searching for articles from Science Direct, Scopus, and Proquest with the keywords